2017
DOI: 10.3945/cdn.117.001636
|View full text |Cite
|
Sign up to set email alerts
|

The Nutritional Status of HIV-Infected US Adults

Abstract: Background: Nutrition is critical to HIV mortality and morbidity. Improved treatment modalities have increased life expectancy of HIV-infected individuals. More than 1 million US adults are living with HIV, but little is known about their nutritional status. Objective: We aimed to characterize the nutritional status of those living with HIV with the use of the NHANES 2003–2014. Methods: The NHANES is a nationally representative, cross-sectional survey of the US population and includes a household interview, me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 33 publications
0
25
0
2
Order By: Relevance
“…Nutritional deficiencies are common among individuals with HIV infections because of factors such as the oxidative state induced by the virus, malabsorption, metabolic alterations, gut infections, and gut barrier dysfunction produced by chronic HIV infection 18 . Our previous study 9 and other epidemiological studies 19,20 have shown that HIV infection is associated with low selenium status.…”
Section: Discussionmentioning
confidence: 93%
“…Nutritional deficiencies are common among individuals with HIV infections because of factors such as the oxidative state induced by the virus, malabsorption, metabolic alterations, gut infections, and gut barrier dysfunction produced by chronic HIV infection 18 . Our previous study 9 and other epidemiological studies 19,20 have shown that HIV infection is associated with low selenium status.…”
Section: Discussionmentioning
confidence: 93%
“…However, this HIV-associated negative effect on serum albumin appeared to extend beyond HIV control as over half of the patients with suppressed viral loads and those with CD4+ cell counts ≥350 cells/μL also had serum albumin levels below 35 g/L at the start of CAPD. HIV is thought to influence serum albumin levels through a number of mechanisms such as chronic inflammation, infections, nutritional deficiencies, chronic gastrointestinal ailments, altered metabolism and absorption of vital nutrients, nutrient-drug interactions, and increased caloric requirements [3134].…”
Section: Discussionmentioning
confidence: 99%
“…Improved treatment modalities play a highly significant role in increasing life expectancy of HIV-infected individuals. Over 1 million adults within the United States live with HIV (Thuppal, Jun, Cowan, & Bailey, 2017). A study was carried out in Kathmandu Valley, Nepal with the aim of estimating the prevalence of under-nutrition among PLWH in Nepal, and also to point out the main risk factors and to evaluate the correlations with PLWHs' quality of life and nutritional status (Thapa, Amatya, Pahari, Bam, & Newman, 2015).…”
Section: Discussionmentioning
confidence: 99%